Insights on wellbeing and society from a Taulasea/traditional healer perspective - Ridvan Firestone; Penina Hitti; Layla Latu; Blakely Brown; Lisa Te Morenga; Nia Aitaoto (Kōtuitui)
Unquestionably there is a need for more Indigenous and traditional knowledge to understand better the link between ‘culture and food systems, diet and traditional practices’ and ‘diet-related diseases’ (e.g. diabetes), particularly from a Pacific worldview. In this study, we explored the role of Samoan traditional healers or Taulasea with the research question: ‘What insights are contained in Indigenous and traditional knowledge systems that can be used to design new ways to prevent diet-related diseases among Samoans (and Pacific peoples in general) in NZ?’ Fourteen Taulasea participated in semi-structured narrative interviews (talanoa methodology) from June 2022 to October 2023. Transcribed interviews were coded and analysed using thematic analysis. Four major themes were revealed that examined the sacredness of their knowledge and practice, Taulasea specialisation, treatment methods and holistic views that impact health. These insights highlight why Samoans continue to use traditional healing as the first port of call for their health needs.Glossary of Samoan/Māori words: Fa'afaletui: a Samoan research framework used to weave different perspectives together based on the different groups of individuals interviewed; Fofo: traditional massage; Va: relational space; Vai: traditional medicines based on plants; Talanoa: Pacific methodology approach of weaving the discussion points in qualitative research using semi-structure interviews; Taulasea: traditional healer/practitioner; To'ala: a life-essence that resides in the upper torso of a healthy individual. Healers usually palpitate for the to'ala to see if it is in place or mis-aligned; Rongoā: traditional Māori medicine; mirmiri: massage; karakia: prayers, chants or incantations.